Novel Drug Delivery System Based on Docetaxel-loaded Gelatin Nanoparticles Treatment in Human Breast Cancer Cell Line MCF-7 - Jain, Alok Pal (Asian Journal of Pharmaceutics (AJP), 2017)
Background: The goal of the present investigation was to evaluate docetaxel (DOC)-loaded gelatin nanoparticles for cancer therapy. Materials and Methods: DOC-loaded gelatin nanoparticles using ultraviolet-visible spectroscopy, X-ray diffraction, particle size and size distribution, scanning electron microscopy, drug entrapment efficiency, infrared, and in vitro drug release were characterized. The viability of MCF-7 breast cancer (BC) cells was determined by MTT. Cell sensitivity to drugs and growth curves were measured by MTT assay. Changes of cell morphology and ultrastructure were examined by optical and electron microscopy. Results: Solubility, crystallinity, and the crystal properties of an active pharmaceutical ingredient play a critical role in the value chain of pharmaceutical development, manufacturing, and formulation. The rate of drug release for formulation stored at 45°C ± 1°C was increased as compared with the fresh formulation; it might be due to the formation of more pores in the nanoparticles due to evaporation of residual amount of solvent. The in vitro release studies of drug-loaded nanoparticles were conducted at 37 ± 0.5 and 100 rpm using phosphate buffer pH 7.4 (900 ml) in a USP dissolution apparatus under sink condition. DOC-loaded gelatin nanoparticles depleted the viability of MCF human breast cell line. In this study, MCF BC cell line revealed growth inhibition in a dose-dependent manner when treated DOC-loaded gelatin nanoparticles at concentrations ranging from 5 to 100 μg. Conclusion: The DOC-loaded gelatin nanoparticles displayed differential cytotoxicity toward MCF7 cancer cells. These biogenic nanoparticles are biocompatible and found to be good candidates for sustained drug delivery in diseases like cancer.